ChemInform Abstract: Practical Synthesis of 4‐Benzylidene ‐2‐Phenyl‐5(4H)‐oxazolones. Issue 43 (7th October 2013) - Siddaiah, V.; Basha, G. Mahaboob; Sudhakar, D.; Srinuvasarao, R.; Kumar, Y. Santosh
Abstract via simple reaction of hippuric acid (I) with various aldehydes (II)